ANALYSIS OF BREAK EVEN POINT AND MARGIN OF SAFETY AS A BASIS FOR PROFIT PLANNING AT PT UNILEVER INDONESIA TBK IN 2017-2021 - Dailami, Ahmad; Kardofa, Mochamad; Saputra, Jumadil (iora, 2024)
Earning profit or profit is the main goal of establishing a company. To know how much budget needs to be spent to achieve the goal, the profit must be calculated first. Break even point (BEP) analysis is one of the tools to determine the estimated profit from the sale of the products offered. However, a high margin of safety (MOS) will protect the company from the risk of loss. The purpose of this study is to determine the profit planning for PT Unilever Indonesia Tbk. The method used is a descriptive quantitative method with a case study approach. From the research that has been done, the results show that sales have exceeded the predetermined BEP, as well as the MOS value obtained has a positive trend or an increase. In order to get more maximum results or profits the company needs to also pay attention to achieving sales targets. The target can be achieved if the company can make cost efficiency and increase sales volume.